Stress Experienced by Special Education Teachers and Coping with Stress - Abdullah Sadan; Fulya Akgül; İsmail Çelik; Özcan İkbal; Serkan Atilla; İbrahim Kuz; Gökmen Keklik (Ömer Gökhan Ulum, 2023)
The main purpose of the research is to examine the stress factors of special education teachers. The sample of the research consists of special education teachers working in special education schools in a district in the Aegean Region. Pearson correlation analysis, t test and ANOVA test were used to analyse the data in the research in which quantitative research methods were used. As a result of the research, it is seen that the inadequate salary of the teachers, ignoring the individual differences of the students in the course curriculum, perception of teaching as a profession that "everyone can do", and students' lack of interest in the lesson partially affect the stress level. There is a positive, moderately strong relationship between the student dimension and the personality dimension, curriculum dimension, teacher/teacher relations dimension, management/supervision dimension, school dimension and professional dimension. There is a moderately strong positive relationship between School Dimension and Occupational Dimension. There is no statistically significant difference between all dimensions of stress factors in terms of gender, marital status, type of school graduated from, reason for choosing teaching profession and length of service.